One year of downwelling spectral radiance measurements from 100 to 1400 cm−1 at Dome Concordia: Results in clear conditions. Issue 18 (28th September 2016) - Rizzi, R.; Arosio, C.; Maestri, T.; Palchetti, L.; Bianchini, G.; Del Guasta, M.
Abstract: The present work examines downwelling radiance spectra measured at the ground during 2013 by a Far Infrared Fourier Transform Spectrometer at Dome C, Antarctica. A tropospheric backscatter and depolarization lidar is also deployed at same site, and a radiosonde system is routinely operative. The measurements allow characterization of the water vapor and clouds infrared properties in Antarctica under all sky conditions. In this paper we specifically discuss cloud detection and the analysis in clear sky condition, required for the discussion of the results obtained in cloudy conditions. First, the paper discusses the procedures adopted for the quality control of spectra acquired automatically. Then it describes the classification procedure used to discriminate spectra measured in clear sky from cloudy conditions. Finally a selection is performed and 66 clear cases, spanning the whole year, are compared to simulations. The computation of layer molecular optical depth is performed with line‐by‐line techniques and a convolution to simulate the Radiation Explorer in the Far InfraRed‐Prototype for Applications and Development (REFIR‐PAD) measurements; the downwelling radiance for selected clear cases is computed with a state‐of‐the‐art adding‐doubling code. The mean difference over all selected cases between simulated and measured radiance is within experimental error for all the selected microwindows except for the negative residuals found for all microwindows in the range 200 to 400 cm −1, with largest values around 295.1 cm −1 . The paper discusses possible reasons for the discrepancy and identifies the incorrect magnitude of the water vapor total absorption coefficient as the cause of such large negative radiance bias below 400 cm −1 . Key Points: Downwelling radiance spectra measured during 2013 by a FTS Spectrometer at Dome C, Antarctica Results in clear conditions are fundamental to derive clouds infrared properties in FIR microwindows Results in clear conditions show that the computation of H2O total absorption from 200 to 400 cm‐1 require revision